THE MILL TRADITIONAL CRAFTS OF DAGESTAN: ETHNIC CULTURE, TERMINOLOGY - Magomedov, Amirbek Dzalilovic; Usupov, Hizri Abdulmazidovic (History, Archeology and Ethnography of the Caucasus, 2021)
The article is devoted to the characteristics of the traditions of mill crafts in Dagestan, their development in the historical perspective. The topic is poorly researched. At the same time, there are valuable observations on the topic made by Dagestani ethnographers. Admittedly, "mill" adaptations and crafts appear with the advent of agriculture, and crafts using water mills begin to develop in the conditions of arable farming. The design of water mills with a horizontal turbine is considered an invention of the Caucasian peoples. Watermills in Dagestan in the conditions of mountain rivers have become widespread. Researchers attribute the emergence of such crafts in Dagestan to the beginning of a new era. Written sources about such mills belong to the middle of the XIV century. On the basis of linguistic (terminology) materials, we can make a cautious conclusion that initially watermills were widespread in the Dagestan foothills. Then they spread to the mountain zone. The mill industries of Dagestan can be divided into flour-milling, grain-milling, and production of oils, pastes (urbech) from fruit seeds (apricot seed oil was especially popular), cereals (flax, hemp), oilseeds (sunflower), vegetables (pumpkin), and others.In the past, if a river flowed near the village, water mills were actively built. They were in every village and often there were several of them. In addition to public mills, there were privately owned and owned by individual tukhums mills. Water mills in Dagestan "survived" until the end of the twentieth century. Presumably in EIGHTEENTH and early NINETEENTH century in the plains and foothill zone of Dagestan began to spread of water mills with a vertical turbine, borrowed from Russian. In the twentieth century, steam, electric, and windmills were also used here. Today, historic watermills are still used in a number of places to make traditional urbecha paste (oil) and rarely flour.
Keywords: grist mill; hand mill; water mill; flour mills; evolution of traditional milling in the twentieth century.